Was UEFA’S Goal of an Environmentally Friendly Euro 2020/21 a Success? - Komen, Boaz; Skandrani, Hanine; Myagmarjav, Ariuntuya; Ungvárai, Ádám (International Journal of Engineering and Management Sciences, 2022)
The football Euro 2020/21 has been said to be more environmentally friendly, as it was spread all over Europe, thus no new stadiums needed to be built. On the other hand, more traveling became necessary. How does these effects behave with each other? Was the attempt to reduce emissions successful?       This paper seeks to compare the goals for UEFA 2020/21 for environmental friendliness and its success. A mixed research strategy was adopted in this paper where qualitative analysis was done on existing literature review and also quantitative approach where assumptions were drawn from literature review to estimate the environmental impact. This paper found that UEFA's initial estimate of 425,000 tons of carbon dioxide emissions in traveling for the Euro Cup 2020 was a bit higher than the actual amount of carbon emissions from our calculation of 143,531 tons. What stands out is that its findings agree with UEFA's estimate that Euro Cup 2020 emissions were lower than that of 2016 which emitted 517,000 tons of carbon dioxide for traveling. This gives a greater reason to conclude that UEFA met its goal of reducing carbon emissions. The overall carbon dioxide emissions in traveling and constructing stages were 1,275,988 tons in Euro Cup 2020 and 2,803,000 tons in Euro Cup 2016. This further affirms the overall carbon dioxide emission reduction by half in Euro Cup 2020 as compared to Euro 2016. From our findings, we can conclude that the Euro Cup 2020 indeed succeeded in reducing overall carbon dioxide emissions by half. Despite the success, this paper views that the carbon emissions are still high for a single event and hence there is room for reduction of carbon emissions to lower levels as possible. we can conclude that the Euro Cup 2020 indeed succeeded in reducing overall carbon dioxide emissions by half. Despite the success, this paper views that the carbon emissions are still high for a single event and hence there is room for reduction of carbon emissions to lower levels as possible. we can conclude that the Euro Cup 2020 indeed succeeded in reducing overall carbon dioxide emissions by half. Despite the success, this paper views that the carbon emissions are still high for a single event and hence there is room for reduction of carbon emissions to lower levels as possible.